"I was never trained to do any of that" – personalisation and the impact of the "customer" on employment relations in voluntary sector social care. Issue 5 (2nd April 2020) - Young, Doug
Abstract : Purpose: The purpose of this paper is to examine the extent and impact of customer-oriented norms on employment relations in voluntary sector social care, within the context of personalisation. Self-Directed Support (SDS) is premised on the notion that customer-led care enhances autonomy among service users and therefore improves quality of life, and additionally, gives employees more discretion in their work. However, by attempting to improve quality of service without additional funding – and in many instances, with funding cuts – it can be argued that SDS is in practice effectively attempts to achieve "more-for-less." This paper examines the effect of this dynamic on employment relations, using the organisation as the unit of analysis. Design/methodology/approach: This paper examines the existing literature on personalisation and SDS, and positions it alongside the sociology of service work. Particular focus is given to Korczynski's notion of Customer-Oriented Bureaucracies (COB). Data collection took place in four comprehensive case studies, comprised of fifty-five semi-structured interviews overall and a benchmarking survey of each. Findings: Findings demonstrate that the influence of customer-oriented norms only affected certain features of the employment relationship, and tended to result from pressures other than service users, such as organisational strategy or funding constraints. In consequence, none of the individual case studies fit the description of COB in its absolute form. Instead, what can be observed is a strong pattern of influence across specific dimensions of the employment relationship. In relation to policies and procedures, the impact of customer-oriented norms was experienced in 70% of instances, 83.3% of incidences pertaining to terms and conditions, and 85.7% of incidences pertaining to work organisation. Research limitations/implications: The data itself is limited to fifty-five interviews across four case studies, and so only gives a "snapshot" of employee relations within the sector. Further research would be advantageous to address these issues geographically and temporally. Practical implications: Firstly, it contributes academically to existing bodies of literature on both voluntary sector social care and the sociology of service work. Secondly, it provides practitioners with analysis of the issues that accompany personalisation, and how adopting customer-oriented norms impacts the employment relationship. Thirdly, it demonstrates to legislators and commissioners that existing shortfalls in funding are compensated for by the above-and-beyond efforts of those who work in the sector, and that this is an increasingly untenable situation. Social implications: This paper sheds much needed light onto employment relations in the doubly under-researched areas of voluntary sector social care in Scotland. It attempts to aid employee relations pertaining to the often low paid social care workforce, and the care of service users who include the most vulnerable in society. By identifying potential issues pertaining to employee relations, it seeks to avoid future disruptions to service provision which could have adverse effects on organisations, employees, and service users. Originality/value: This paper makes a theoretical and conceptual contribution by utilising the sociology of service work as a means of better understanding employment relations in voluntary sector social care. It compares the impact of customer-oriented norms across four distinctly different service provision types Furthermore, the segmenting of findings across three key areas of employment relations allows for a systematic analysis which pinpoints the presence and extent of customer-oriented norms and their influence on the employment relationship.